2005
DOI: 10.1074/jbc.m504050200
|View full text |Cite
|
Sign up to set email alerts
|

Goodpasture Autoantibodies Unmask Cryptic Epitopes by Selectively Dissociating Autoantigen Complexes Lacking Structural Reinforcement

Abstract: Rapidly progressive glomerulonephritis in Goodpasture disease is mediated by autoantibodies binding to the non-collagenous NC1 domain of ␣3(IV) collagen in the glomerular basement membrane. Goodpasture epitopes in the native autoantigen are cryptic (sequestered) within the NC1 hexamers of the ␣3␣4␣5(IV) collagen network. The biochemical mechanism for crypticity and exposure for autoantibody binding is not known. We now report that crypticity is a feature of the quaternary structure of two distinct subsets of ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 32 publications
(49 reference statements)
1
67
0
Order By: Relevance
“…28 AAV has provided a model for discovery of characteristic features of autoimmune diseases. Investigations exemplify how environmentally triggered effects [29][30][31][32] might alter epigenetic mechanisms 33 that result in a deviation in expression and availability of the actual autoantigens recognized in disease.…”
Section: Discussionmentioning
confidence: 99%
“…28 AAV has provided a model for discovery of characteristic features of autoimmune diseases. Investigations exemplify how environmentally triggered effects [29][30][31][32] might alter epigenetic mechanisms 33 that result in a deviation in expression and availability of the actual autoantigens recognized in disease.…”
Section: Discussionmentioning
confidence: 99%
“…Only ␣3NC1 monomers elicited murine antibodies with similar specificity to human GP autoantibodies, thus implicating ␣3NC1 monomers as the antigen initiating autoimmune anti-GBM disease. Consistent with this paradigm, GP antibodies were shown to target preferentially a subset of M-␣3␣4␣5 NC1 hexamers composed of monomer subunits only, inducing hexamer dissociation upon binding (29). Surprising, immunization with acid-dissociated rather than native NC1 hexamers induced production of mouse antibodies most closely resembling human ARAS alloantibodies and Mab3.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, the epitopes of all GP antibody subsets are cryptic and inaccessible for autoantibody binding unless the hexamer is dissociated (19,29). The most likely explanation for the crypticity of GP epitopes is steric hindrance of key epitope residues by the flanking ␣4NC1 and ␣5NC1 domains (14,29). Indeed, among the four E A residues identified in the epitope of immunodominant GP A antibodies (30), none is proximal to the E B region, whereas two are adjacent (within 10 Å) to the ␣5NC1 domain ( Figure 6).…”
Section: Distinct Locations Of ␣3nc1 Alloepitopes and Autoepitopesmentioning
confidence: 99%
“…Anti-GBM disease is a rare form of autoimmune disorder with significant morbidity and mortality, and is characterized by crescentic glomerulonephritis, often accompanied by pulmonary hemorrhage and the presence of circulating and deposited anti-GBM antibodies [46]. The disease is caused by antibodies against the noncollagenous NC1 domain of the a3 (and, to a lesser extent, the a5) chains of type IV collagen, which contains two conformational epitopes, designated E A and E B [47,48]. The etiology of anti-GBM disease is unclear, but a recent study has suggested that the development of the disease may be considered as an autoimmune ''conformeropathy'' that involves perturbation of the quaternary structure of the a345NC1 hexamer, inducing a pathogenic conformational change in the a3NC1 and a5NC1 subunits [48].…”
Section: Discussionmentioning
confidence: 99%